Cultural Stories and Lexical Choices in the Informal Speech of Sukabumi Teenagers: A Linguistic Ethnography - Sri Rahayu; Eri Kurniawan; Retty isnendes; Ramadani Ramadani; Risa Triarisanti (RETORIKA: Jurnal Ilmu Bahasa, 2025)
This study aims to examine how lexical choices and cultural narratives contribute to the construction of identity in the informal speech of adolescents in Sukabumi. Specifically, it seeks to analyze the ways in which adolescents express local identity, social belonging, and cultural values through their everyday linguistic practices. Using a linguistic ethnographic approach, the research draws on Sociolinguistic Variation Theory (Labov, 1972; Eckert, 2012) and Linguistic Ethnography (Rampton et al., 2015) to explore how variations in language use reflect broader social and cultural dynamics within the community. The research explores how adolescents negotiate between local traditions and global influences in everyday language practices. The study employed a linguistic ethnographic method combining participant observation, recorded natural conversations, and in-depth interviews with adolescents in Sukabumi City and Regency, West Java. This approach enabled an in-context exploration of how language use, cultural narratives, and identity construction emerge in the participants’ everyday interactions. The findings reveal that adolescents’ lexical repertoire consists of four dominant categories: popular youth vocabulary, agrarian and familial lexicon, global borrowings, and emotional-aesthetic terms. These categories demonstrate the dual functions of language as both a communicative tool and a marker of identity and solidarity. Cultural stories emerging from adolescents’ speech reflect kinship ties, agricultural traditions, religious practices, aesthetic self-care, and digital globalization, illustrating the hybridization of local and global values. Furthermore, the grammatical structures of adolescent speech—dominated by simple declaratives, imperatives, ellipsis, and code-mixing—indicate strategies tailored for digital communication and identity projection. Overall, this study concludes that Sukabumi adolescents’ informal speech embodies a process of cultural negotiation and glocalization, wherein traditional values are preserved yet reinterpreted within the framework of modern youth culture. The research contributes theoretically to the study of language, identity, and culture, while providing practical insights for educators, linguists, and policymakers in understanding the sociocultural dynamics of adolescent language use in contemporary Indonesia.